KAIDAH ’URF DALAM PRAKTIK PEMBAYARAN DI RUMAH MAKAN - Arnoldy Arnoldy; Afried Lazuardi (Karimiyah: Journal of Islamic Literature and Muslim Society, 2024)
In everyday life, we often unknowingly engage in muamalah practices that may not be fully in accordance with the teachings of Islam. However, these practices have become a long-standing common habit in society. Islam, as the last religion, provides guidelines for all aspects of human life in the world, including dealing with fellow human beings. Although 'urf is not always agreed upon by all scholars, in fiqh, 'urf is often used as a legal basis in various aspects of daily life that are constantly evolving. This study aims to explore how 'urf is applied in payment practices in many restaurants and food stalls in Indonesia. By using the rules of 'urf in everyday muamalah, customs that may not be fully compliant with sharia law do not always need to be changed. This can provide convenience and comfort when transacting in society without causing difficulties or conflicts.